Decapsulating Brine Shrimp Eggs - Craig Watson; Roy Yanong (EDIS)
Brine shrimp eggs, essential for feeding small fish in hatcheries, require separation from their non-digestible shells and unhatched eggs post-hatching. This document explains the decapsulation process using chlorine removing the outer shell, simplifying separation and sterilizing the eggs. This method improves hatch rates and allows unhatched eggs to be fed directly to fish. The decapsulation procedure involves soaking the eggs in water, treating them with bleach, and rinsing thoroughly. Decapsulated eggs can be stored in brine or hatched immediately in containers with specific conditions. This process adapts to various brine shrimp egg types, ensuring effective hatchery operations. First published June, 1990.